MATERI PEMBELAJARAN ALQURAN PERSFEKTIF WAHDATUL ‘ULÛM PRODI PENDIDIKAN AGAMA ISLAM FITK UIN SUMATERA UTARA - Nasution, Zulkipli (Jurnal Al-Fatih, 2023)
Wahdatul 'Ulum is very urgent regarding the integration of knowledge. A number of Islamic tertiary institutions have transformed into universities with the expansion of scientific fields developed in the hope of providing solutions to problems of civilization and humanity and can give hope for spiritual quality and safety in the future. The State Islamic University of North Sumatra as an Islamic educational institution that has been in the process of integrating knowledge has determined that several courses must be in accordance with the concept of Wahdatul 'Ulûm. One of the subjects that must refer to the concept of Wahdatul 'Ulûm is the Koran. The Qur'an course is a compulsory subject for every faculty and study program at UIN North Sumatra. What is the material for the Koran subject in the Islamic Religious Education Study Program, FITK UIN North Sumatra. The Qur'anic materials in the perspective of Wahdatul 'Ulûm are far different because in general the focus is on reading and memorizing the Qur'an, especially on verses and surahs in the Qur'an juz 30. While the previous material is more broadly about the sciences of the Qur'an and related matters.